The structural integrity assessment of a partially filled tank pertaining to liquid sloshing upon sudden brake applications - Abid, Hasan M.; Shah, Qasim Hussain; Faris, Waleed Fekry (2011)
A liquid cargo contained in a partially filled tank vehicle is known to experience liquid sloshing when subjected to a sudden braking application, which generates liquid forces applied on the tank wall affecting its structural integrity. A cylindrical partially filled tank is modeled in three dimensions using Arbitrary Lagrangian Eulerian (ALE) method in LSDYNA code. The experimental results are compared with the simulation results and demonstrate a good agreement that validate the capability of LS-DYNA method in representing the liquid slosh inside the tank. The study also investigates the effectiveness of baffles that can significantly mitigate the liquid sloshing. In the present study the arrangement and design of the baffles has been proposed that can reduce the sloshing inside the partially filled tank.